2021
DOI: 10.1038/s41598-020-80854-5
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic defense of Cyperus brevifolius in hydrocarbons stress environment and changes in soil properties

Abstract: Hydrocarbons or crude oil contamination of soil is still a burning problem around the globe. The herbs competent that are to survive in hydrocarbons contaminated habitats have some adaptive advantages to cope up with the adverse situations prevailing in that environment. In the present study, the adaptive response of Cyperus brevifolius in the heavily polluted soil with crude oil has been investigated in terms of survivability, changes in productivity, antioxidants, phytochemicals and functional group pro file… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…The shifting in pH towards less acidic condition after plant's treatment could be attributed to the mineralization of oil components in soil. It has been suggested that introduction of plants in contaminated soil enhances the microbial activities which further accelerate the mineralization process in soil (Chakravarty and Deka 2021).The present nding on pH deviation agrees the report of Ukaegbu-Obi and Omeh (2014) who have pointed out that mineralization of crude oil components is responsible for reduction in soil acidity thereby con rming the biodegradation of hydrocarbons in the contaminated soil. Similarly, the soil conductivity and water holding capacity values have also increased signi cantly in T3 when compared with the initial level (T1).…”
Section: Changes In Physico-chemical Parameterssupporting
confidence: 90%
See 3 more Smart Citations
“…The shifting in pH towards less acidic condition after plant's treatment could be attributed to the mineralization of oil components in soil. It has been suggested that introduction of plants in contaminated soil enhances the microbial activities which further accelerate the mineralization process in soil (Chakravarty and Deka 2021).The present nding on pH deviation agrees the report of Ukaegbu-Obi and Omeh (2014) who have pointed out that mineralization of crude oil components is responsible for reduction in soil acidity thereby con rming the biodegradation of hydrocarbons in the contaminated soil. Similarly, the soil conductivity and water holding capacity values have also increased signi cantly in T3 when compared with the initial level (T1).…”
Section: Changes In Physico-chemical Parameterssupporting
confidence: 90%
“…Again, methods of Johnson and Temple (1964) were used to measure the activity of catalase enzyme. Alkaline Phosphatase activities were analyzed by employing the method of Tabatabai and Bremner (1969) whereas polyphenol oxidase and peroxidase were measured by the standard protocols of Bach et al (2013) and German et al (2011).The total population of nitrogen xing, phosphate and potassium solubilizing bacteria in the soil samples were enumerated in Jensen's medium, Pycovskaya's and Aleksandrow agar respectively following serial dilutions technique as outlined by Chakravarty and Deka (2021).…”
Section: Determination Of Enzyme Activity and Bene Cial Bacterial Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…They are used to construct models for the assessment of potential soil fertility [ 28 , 77 , 78 , 79 , 80 ]. Due to their ability to signalize changes triggered under the pressure of stress factors, they also perfectly mirror the effects of pollutants on soil [ 81 , 82 , 83 ]. Among the soil enzymes, dehydrogenases prove best in reflecting the rate of changes in the soil environment.…”
Section: Discussionmentioning
confidence: 99%